Etymological Observations - SIMONYAN, NEKTAR (Bulletin of Yerevan University B: Philology, 2021)
The Armenian roots քեր, քոր dating back to the Indo-European protoform *(s)ker-, (s)kor-, (s)krē- are studied in the article, the forms with determinants –d и t-(քերթել, քերծել) and corresponding roots of other Indo-European languages are introduced. It is supposed, that the words քարթ (score/зазубрина), քարթեղ (grindstone/точило), քարթմա (plugshare / лемех, чересло) existing in the Armenian dialects, also date back to the Indo-European protoform.The Armenian root աղիփ (զաղիփ զաղփաղփուն) as well is studied and it is supposed for it Indo-European protoform *lē̆b, lō̆ b-, lāb.